The hocus girl : a Simon Westow mystery - Nickson, Chris (Nickson, Chris. Simon Westow mysteries, 2020)
"Leeds, May 1822. Thief-taker Simon Westow owes Davey and Emily Ashton everything - the siblings gave him sanctuary when he needed it most. So when Davey is arrested for sedition and Emily begs Simon for help, he starts asking questions, determined to clear his friend. Are the answers linked to rumours of a mysterious government spy in town? Davey's not the only one who needs Simon's help. Timber merchant George Ericsson has been 'hocussed' by a young woman who spiked his drink and stole his valuable ring and watch. Who is she, and how does she know one of Simon's assistant Jane's deepest secrets? The path to the truth is twisted and dangerous. Simon and Jane encounter murder, lies, betrayal and a government terrified of its own people as they attempt to save Davey and find the hocus girl."--Publisher.